71.5k views
2 votes
For the following geometric sequence find the explicit formula {1,-3,9,...}

For the following geometric sequence find the explicit formula {1,-3,9,...}-example-1
User Afeez Aziz
by
5.2k points

2 Answers

5 votes
The first term of this series (a+1) is 1 and the common ratio (r) is -3.

Thus, the explicit formula is a_n = 1*(-3)^(n-1).

Must check this! suppose we try to calculate the 3rd term. Then n = 3.

a_3 = 1*(-3)^(3-1) = (-3)^2 = 9. This is correct.
User Chrisk
by
5.5k points
3 votes

Answer:


a_n=1\cdot (-3)^((n-1))

Explanation:

We have been given a geometric sequence and we are asked to find the explicit formula for our given sequence.

The explicit formula of geometric sequence is in form:
a_n=a_1\cdot r^((n-1)), where,


a_n=\text{nth term of sequence},


a_1=\text{1st term of sequence},


r=\text{Common ratio},


n=\text{Number of term}.

First of all, let us find common ratio of our given sequence by dividing one term by its previous term.


r=(-3)/(1)=-3

We can see that 1st term of our given sequence is 1. Upon substituting our given values in explicit form of geometric sequence we will get,


a_n=1\cdot (-3)^((n-1))

Therefore, the explicit formula for our given sequence is
a_n=1\cdot (-3)^((n-1)).

User Johnnyodonnell
by
4.8k points